The Effect of Interval and Fartlek Training on Endurance of Futsal Players at SMA ABBS Surakarta - Fasa, Bagus Abid Putra; Umar, Fadilah; Gontara, Satria Yudi (Java Mutiara Media, 2025)
This study aims to determine: (1) the effect of interval training on the endurance improvement of futsal players at SMA ABBS Surakarta; (2) the effect of fartlek training on the endurance improvement of futsal players at SMA ABBS Surakarta; and (3) the more effective training method between interval training and fartlek training in enhancing the endurance of futsal players at SMA ABBS Surakarta. This research is a quantitative experimental study. The sample consisted of 20 futsal players from SMA ABBS Surakarta. The research method used was an experimental approach with a two-group pretest-posttest design. The study was conducted over 18 sessions with a training frequency of three times per week. The treatments applied were interval training and fartlek training. The research instrument used was the Bleep Test. Data analysis included prerequisite tests (normality test using the Shapiro-Wilk test) and hypothesis testing using the Paired Sample T-Test. The results of data analysis showed that: (1) there was a significant improvement in endurance among futsal players at SMA ABBS Surakarta after undergoing interval training, as evidenced by a Sig. (2-tailed) value of 0.000 < 0.05; (2) there was a significant improvement in endurance among futsal players at SMA ABBS Surakarta after undergoing fartlek training, also evidenced by a Sig. (2-tailed) value of 0.000 < 0.05; and (3) both interval and fartlek training methods were equally effective in improving the endurance of futsal players at SMA ABBS Surakarta, as indicated by a non-significant difference with a Sig. (2-tailed) value of 0.622 > 0.05. The improvement can also be seen from the percentage increase in endurance performance. Based on these findings, it can be concluded that: (1) Interval training has a significant effect on improving the endurance of futsal players at SMA ABBS Surakarta; 2) Fartlek training has a significant effect on improving the endurance of futsal players at SMA ABBS Surakarta; (3) Both interval and fartlek training methods are equally effective in enhancing the endurance of futsal players at SMA ABBS Surakarta, as no significant difference was found between the two training methods.